Efeitos da fotobiomodulação associada à reabilitação vestibular no tratamento de pacientes com sintomas vestibulares e zumbido - Goes, Thales Roges Vanderlei de (2023)
Vestibular symptoms and tinnitus are extremely common in clinical practice and can occur simultaneously or independently. Vestibular Rehabilitation (VR) is a consolidated treatment in the literature for vestibular dysfunctions, tinnitus presents several therapeutic possibilities, with different degrees of success. Currently, photobiomodulation (FBM) has been identified as a therapeutic option, however there is no consensus in the literature on this matter, especially when it comes to patients with tinnitus associated with dizziness. Objective: (1) investigate whether there is an immediate electrophysiological effect of FBM on potentials (ECochG and BAEP), in order to validate the dosage used in the clinical trial; (2) investigate whether there is an effect of FBM associated with VR in the treatment of patients with vestibular symptoms and tinnitus. Method: Dissertation structured in two articles. (1) experimental study, randomized cross-over, with a sample of 60 ears, divided into Research Group (GP) and Control Group (CG), a transmeatal FBM protocol was used with pre- and post-test evaluation immediately upon application, for through electrophysiological measurements in GP and GC. (2) Triple-blind randomized clinical trial, with a sample of 20 subjects with vestibular symptoms and tinnitus, randomly divided into GP (RV + active FBM) and CG (RV + FBM placebo), ten sessions of therapeutic intervention were carried out, twice a week for five weeks. The T and Mann-Whitney tests were used to compare the records. Results: (1) A significant effect of FBM was observed between the GP and CG, in the analysis of the amplitude of the summation potential and in the area and amplitude relationships between the summation and action potentials. (2) The two groups showed significant differences in the reassessment, in relation to the vestibular symptoms instruments, but only the GP group showed an improvement in tinnitus scores. Regarding the intergroup analysis of vestibular symptoms, the GP showed improvement in the parameters of the ocular vestibular reflex, sensory analysis of vestibular function and stability limit in relation to the CG. Conclusion: An influence of the immediate FBM effect on the ECochG potential was observed. FBM associated with VR contributed to reducing tinnitus discomfort and improving vestibular parameters compared to CG.